Examining transport needs in the Global South using a screening framework - Caulfield, Brian (My University, 2020)
Despite the increasing emphasis on the social aspects of transport externalities in the global agenda of public policies (UN, 2016), transport appraisals (ex-ante) are still strongly driven by economic and environmental analysis only (Geurs et al. 2009; Jones and Lucas 2012). In this context, the goals targeting poverty reduction and social well-being promotion become fundamentally undermined when the social impacts are overlooked in the decision-making process of transport development (Vasconcellos 2003; World Bank 2006; Jones and Lucas 2012; Jones et al. 2013). Hence, in a context where the transport-related needs have been either disregarded, not fully captured, or addressed by subjective approaches, the proposition of an objective and well-grounded screening framework of transport needs can play a pivotal role in making transport planning more socially inclusive. The framework that is proposed applies the Analytic Hierarchy Process (AHP) and spatial autocorrelation techniques to provide tools and evidence-based guidelines that can guide transport interventions in Northeast Brazil to become more effective in reducing poverty. While the socially driven framework that is outlined here focuses on the transport needs of Northeast Brazil, it can also be replicated in other developing countries facing similar socio-economic and transport challenges. The results show that different regions of Northeast Brazil suffer differently from externalities and that sub-regional analysis is needed.
PUBLISHED
Keywords: Smart & Sustainable Planet; Policy; Transport